Optimization of Pharmaceutical Supply Chain Resilience in Post-Pandemic Era - Nolbert, Andi; Samuel, Buyako (Yayasan Gema Bina Nusantara, 2025)
The global pharmaceutical industry has faced unprecedented disruptions due to the COVID-19 pandemic, exposing significant vulnerabilities in traditional supply chain models. This research, titled